Tpd3‐Pph21 phosphatase plays a direct role in Sep7 dephosphorylation in Candida albicans. Issue 1 (20th April 2016) - Liu, Qizheng; Han, Qi; Wang, Na; Yao, Guangyin; Zeng, Guisheng; Wang, Yanming; Huang, Zhenxing; Sang, Jianli; Wang, Yue
Summary: Septins are a component of the cytoskeleton and play important roles in diverse cellular processes including cell cycle control, cytokinesis and polarized growth. In fungi, septin organization, dynamics and function are regulated by phosphorylation, and several kinases responsible for the phosphorylation of several septins have been identified. However, little is known about the phosphatases that dephosphorylate septins. Here, we report the characterization of Tpd3, a structural subunit of the PP2A family of phosphatases, in the pathogenic fungus Candida albicans . We found that tpd3Δ/Δ cells are defective in hyphal growth and grow as pseudohyphae under yeast growth conditions with aberrant septin organization. Western blotting detected hyperphosphorylation of the septin Sep7 in cells lacking Tpd3. Tpd3 and Sep7 colocalize at the bud neck and can coimmunoprecipitate. Furthermore, we discovered similar defects in cells lacking Pph21, a catalytic subunit of the PP2A family, and its physical association with Tpd3. Importantly, purified Tpd3‐Pph21 complexes can dephosphorylate Sep7 in vitro . Together, our findings strongly support the idea that the Tpd3‐Pph21 complex dephosphorylates Sep7 and regulates morphogenesis and cytokinesis. The tpd3Δ/Δ mutant is greatly reduced in virulence in mice, providing a potential antifungal target. Abstract : Septins are a component of the cytoskeleton and play important roles in cell cycle control, cytokinesis, and polarized growth. In fungi, septin organization and function are regulated by phosphorylation. Here, we demonstrate the PP2A family Tpd3‐Pph21 phosphatase dephophorylates the septin Sep7 in the fungal pathogen Candida albicans, which is important for morphogenesis, cytokinesis, and virulence.